Effects of cooking methods and tea marinades on the formation of benzo[a]pyrene in grilled pork belly (Samgyeopsal) - Park, Keun-Cheol; Pyo, HeeSoo; Kim, WooSeok; Yoon, Ki Sun (ELSEVIER SCI LTD, 2017)
We investigated the effects of different grilling tools, temperatures, and tea marinades on the formation of benzo[a]pyrene in grilled pork belly as well as the antioxidant capacities of tea marinades. The least amount of benzo[a]pyrene was detected in modified charcoal-grilled pork belly (1.28 mu g/kg). The highest risk factors for the formation of benzo[a]pyrene are direct contact with flames and fat excess on the heating source. A modified charcoal grill can be used as an alternative grilling tool to meet consumer needs for safety and taste. The marination of pork bellies with tea increased radical-scavenging activity and prevented lipid oxidation in proportion to the concentration of tea infusion and marinating time. The yerba mate tea marinade significantly increased the radical-scavenging activity and prevented benzo[a]pyrene formation more than the green tea marinade. Tea marinade can be applied to seasoning or sauce as pretreatment to preserve the quality of meat and to decrease benzo[a]pyrene formation during cooking. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: POLYCYCLIC AROMATIC-HYDROCARBONS; MATE ILEX-PARAGUARIENSIS; ANTIOXIDANT ACTIVITY; GREEN TEA; EXTRACTS; STABILITY; MEAT; COMPOUND; AMINES; IRON